Effect of Treatment with Humic Acid on Some Growth Characteristics and Protein Content in Different Varieties Vicia faba L. Plant - Mohamad, Maisam Ammar; Al-Bayaty, Ayyub Juma Abdl-Rhmaan (South Eastern European Journal of Public Health, 2024)
An experiment was carried out using plastic pots in the 2023-2024 season to evaluate the method of treatment with humic acid in the growth characteristics and protein percentage of different varieties of faba bean plants. The study included two factors, the method of adding humic acid (without acid, spraying acid on the plant, adding acid to the soil). The second factor included four varieties of beans (local Iraqi, Netherland, Spanish, and French). The results showed: superiority of the treatment of adding Humic acid to the soil in terms of plant height, total chlorophyll percentage, number of leaves, and protein percentage by 13.25% and 7.59 mg g-1 wet weight. 6.78% and 8.75%, respectively Compared to the control treatment, the local variety was superior in the characteristics of plant height and number of leaves by 31.72 and 7.26% compared to the French variety, which was superior in the characteristics of number of leaves and protein percentage by 12.27 and 24.0%, respectively. The interaction also outperformed adding acid to the local variety in plant height. By 53.13%, the French variety with added acid exceeded the characteristics of number of leaves and protein percentage by 26.40 and 30.50%, respectively.